Relacje nauczyciel i dziecko w metodzie Reggio Emilia = Relations teacher and child in the Reggio Emilia method - Ławecki, Tymoteusz (Zielona Góra: Uniwersytet Zielonogórski, Wydział Pedagogiki, Psychologii i Socjologii)
This article deals with the relationship between the teacher and the child in the Reggio Emilia approach. It describes the main assumptions of the innovative method of working with a kid. The article outlines how this approach develops the creativity, creation and independence of the educational entities. It is emphasized that one of the most important attribute is the cooperation of all persons involved in the educative and educational process, which document and analyze the didactic activity of the students. In addition, the author has considered the application of this method to the implementation of the objectives of the core curriculum of pre-school education in Poland.
Keywords: edukacja przedszkolna; Reggio Emilia; metoda projektów; współpraca z rodzicami; pre-school education; project-based learning; partnership with parents